2012
DOI: 10.1111/j.1758-5872.2012.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress among parents of children with attention deficit hyperactivity disorder, a Malaysian experience

Abstract: Stress has marked consequences on any person and has important bearings on their mental health. Stress among parents needs be looked into when treating children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
2
6
0
2
Order By: Relevance
“…This also may be attributed to the child’s conduct problems, or poor academic performance that does not meet parental expectations. Also, this may be related to parental stress as Narkunam, Hashim, Sachdev, Pillai, and Ng (2012) found that severe ADHD symptoms is significantly associated with parental stress.…”
Section: Discussionmentioning
confidence: 99%
“…This also may be attributed to the child’s conduct problems, or poor academic performance that does not meet parental expectations. Also, this may be related to parental stress as Narkunam, Hashim, Sachdev, Pillai, and Ng (2012) found that severe ADHD symptoms is significantly associated with parental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Destaca-se que a totalidade dos cuidadores primários das crianças participantes do estudo foi do sexo feminino o que está em concordância com outros estudos que indicam a mulher como a principal responsável pelo cuidado (Romagnoli, 2006;Santos & Cardoso, 2015;). Dentre as cuidadoras, a maioria, tanto no grupo de comparação (G2 = 90,0%), quanto no grupo clínico (G1 = 80,0%) foram as mães das crianças, corroborando outros trabalhos de investigação (Estevam, Marcon, Antonio, Munari & Waidman, 2011;Narkunam, Hashim, Sachdev, Pillai & Guan Ng, 2014;Santos & Cardoso, 2015) Somado a esses dados observou-se que as cuidadoras das crianças do G1 possuiam até 40 anos de idade (55,0%), pouca escolaridade (65,0% com menos de 8 anos de estudo), a maioria trabalhava fora de casa (65,0%) e 95,0% delas recebiam menos de dois salários mínimos. Pode-se refletir sobre o papel que é depositado e assumido dentro da família pela mulher no cuidado com os filhos e a sobrecarga advinda por ter responder, além das demandas domésticas de cuidado à família, as demandas do trabalho, caracterizando desse modo uma dupla jornada.…”
Section: Discussionunclassified
“…Nevertheless, a study conducted by some Malaysian psychologists found that parents whose children have been in contact with the PAC Unit (Psychiatry Adolescent and Child) for two years or more are actually more stressed than those whose children have two years or less duration of contact (Narkunam et al, 2014).To optimize the effectiveness of the available service, it requires parents to adopt adaptive approaches and attitudes. This study identified some approaches that empower Chinese parents to remain positive towards all interventional decision.…”
Section: Discussionmentioning
confidence: 99%